Description of Integrated Science Process Skills in Physics Education Students in Convex Mirror Practicum - Sinta Oktavia; Utari Prisma Dewi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2020)
This study aims to determine the description of students towards the use of ICT-based convex mirror material guidebooks. The population of this study was the students of the Jambi University physics education class program in 2018. The sampling technique used total sampling, so that the sample of this study was all physical education students at the University of Jambi with 105 students in class 2018 Indicators of observed process skills included the identification of variables, making tables data, Make a graph, Explain the relationship between variables, Obtain and process data, Analyze investigations, Make hypotheses, Identify variables by ovational, design experiments, and conduct experiments. Process skill data is measured through a basic physics practicum performance evaluation sheet, when practitioners conduct convex mirror practicum activities. Data were analyzed using descriptive statistics. The analysis shows that the average Science Process Skills are categorized as good and very good, this shows that students have mastered the integrated Science Process Skills. The results of this study are expected to be a consideration for physics study programs to conduct related studies for other practicum subjects.